The Use of Vocabulary Learning Strategies among Undergraduate Engineering Students: A Case Study - Talpur, Quratulain; Umrani, Tariq Hassan; Umrani, Sumera (Pakistan Languages and Humanities Review, 2025)
The English language is considered the strongest language in the world, and people are attempting to get expertise in this prestigious language (Fatima & Pathan, 2016). Therefore, acquiring proficiency in it demands sound vocabulary knowledge. This study is an attempt to investigate the most and least frequently employed vocabulary learning strategies among undergraduate engineering students of MUET, Shaheed Zulfiqar Ali Bhutto Campus, Khairpur. The sample size was one hundred students enrolled in the first and second years of their study. The data were gathered through a VLSQ adopted from Intaraprasert (2003). The findings revealed that guessing the meaning from clauses was the most frequently employed strategy for vocabulary learning. Whereas, taking an extra job at offices, etc., is the least frequently used VLS to expand their vocabulary knowledge. It is recommended that language instructors should be aware of their students’ use of various VLS approaches to make them autonomous.